Indonesia youth population norms for EQ-5D-Y-3 L, EQ-5D-Y-5 L and the PedsQL generic core scale: lower health related quality of life relates to high economic status and stress - Titi Sahidah Fitriana; Fredrick Dermawan Purba; Elly Stolk; Jan J. V. Busschbach (BMC, 2023)
Abstract Background The availability of population norms from generic health-related quality of life (HRQoL) instruments can support the interpretation of health outcomes. This study aimed to provide Indonesian youth population norms for the generic HRQoL measures: EQ-5D-Y-3 L, EQ-5D-Y-5 L, and the PedsQL Generic Core Scales. In addition the opportunity arising from the generation of a large representative sample was taken to explore the relationships between HRQoL, health, and socio-economic factors. Methods A representative sample of 1103 Indonesian children (aged 8-16 years) completed EQ-5D-Y-3 L, EQ-5D-Y-5 L, the PedsQL Generic Core Scales, and questions related to demographic data and self-reported health status. A stratified quota sampling design was used to represent Indonesian children in terms of residence, age, gender, and geographical area. Family expenses per capita per month were retrieved from parents to determine a child's economic status. Results The total sample was representative of the Indonesian youth general population. The proportions of participants who reported problems were 43.35% (EQ-5D-Y-3 L), 44.10% (EQ-5D-Y-5 L), and 94.93% (PedsQL Generic), with 31.7% of children reporting health complaints. Older children (13-16 years) reported more problems than younger children (8-12 years). Children living in urban areas reported more problems than children living in rural areas. The lowest value health state reported was '12332' (valued at 0.54), and the minimum EQ VAS score was 60.00. Moderate correlations were found between EQ-5D-Y-3 L values to EQ VAS scores and to PedsQL Total Score. Hierarchical regression analysis showed that females, older age, and having health complaints contributed to a lower level of HRQoL as measured by EQ-5D-Y-3 L values, EQ VAS, and PedsQL Total Score. Remarkably, children with high economic status had lower EQ VAS and PedsQL Total Scores. Among symptoms, 'having stress' had the largest influence with respect to lower EQ-5D-Y-3L values, EQ VAS, and PedsQL Total Score. Conclusions Population norms for children's HRQoL as measured by EQ-5D-Y-3 L, EQ-5D-Y-5 L, and the PedsQL Generic Scales are now available for Indonesia. Age, gender, economic status, and health complaints were related to children's HRQoL. These results provide a basis for health studies and health policy for the youth population of Indonesia.